The Effects of Inflation and Income Taxes on Interest Rates: Some New Evidence - Yun, Young-Sup (Journal of Financial and Quantitative Analysis, 1984)
This paper reexamines the empirical relation between inflation and interest rates concentrating on the tax effect proposed by Darby and Feldstein. Using the random walk intercept model, relative responses of taxable yields and tax-exempt yields to expected inflation are estimated. The results show that for the sample period 1953–1982, the nominal yields on Treasury bills rise at a rate greater than one-for-one with expected inflation, while the nominal yields on default-free municipal bonds rise approximately one-for-one with expected inflation. Thus, the tax-adjusted Fisher hypothesis by Darby and Feldstein is empirically supported. The components of Treasury bills are also extracted and their variances are compared. It is shown that variation of expected inflation is not overwhelmingly larger than that of the after-tax real rate. Therefore, on an after-tax basis, changes in the real rate explain a substantial portion of changes in the nominal rate of interest.